2016
DOI: 10.4103/0970-9185.194765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intubating laryngeal mask airway and fiberoptic bronchoscopy for endotracheal intubation in patients undergoing cervical discectomy

Abstract: Background and Aims:Direct laryngoscopy is hazardous in patients with cervical posterior intervertebral disc prolapse (PIVD) as it may worsen the existing cord compression. To achieve smooth intubation, many adjuncts such as fiberoptic bronchoscope (FOB), video laryngoscopes, lighted stylets, and intubating laryngeal mask airways (ILMAs) are available. However, there is a paucity of literature comparing ILMA with fiberoptic intubation in patients with PIVD. Hence, this study was designed to compare the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Recently, clinical application of video laryngoscopy has been very helpful in resolving difficult intubation cases [ 1 ]. Moreover, the method of intubation after the insertion of a supraglottic device, such as a laryngeal mask airway, is also applied [ 4 ]. Meanwhile, the flexible fiberoptic scope has been in use for some time to resolve difficult intubation situations, and is especially useful for awake intubation [ 3 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, clinical application of video laryngoscopy has been very helpful in resolving difficult intubation cases [ 1 ]. Moreover, the method of intubation after the insertion of a supraglottic device, such as a laryngeal mask airway, is also applied [ 4 ]. Meanwhile, the flexible fiberoptic scope has been in use for some time to resolve difficult intubation situations, and is especially useful for awake intubation [ 3 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…When oral intubation with a direct laryngoscope fails, other airway management devices may be considered if mask ventilation is possible. Video laryngoscope [ 1 ], light wand [ 2 ], fiberoptic scope [ 3 ], or a supraglottic device [ 4 ] may be used; however, the most appropriate choice may be to use the method that the anesthesiologist is most familiar with and in which there is the greatest confidence in a successful outcome. Depending on the situation, a nasal intubation may be attempted, rather than an oral intubation, if the former is believed to be more favorable than the latter.…”
mentioning
confidence: 99%
“…Kolli S et al [13] compared ILMA with fiberoptic bronchoscope for intubation of patients prepared for cervical discectomy and demonstrated that success rate was 100% in each group, 10% in each group required 2 intubation attempts, the time needed for intubation was significantly longer with ILMA (38.1 ± 11.5 s) and the incidence of sore throat was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, we identified and retrieved 18 randomized clinical trials for inclusion evaluating 1972 patients ( Figure 1). Table 1 Three trials were judged to be at low risk of bias, 12-14 13 at unclear risk [15][16][17][18][19][20][21][22][23][24][25][26][27] and 2 at high risk. 28,29 Random sequence generation was assessed as low risk of bias in 16 trials, allocation concealment in 9 trials, completeness of outcome data in 8 trials, selective outcome reporting in 4 trials and other bias in 15 trials ( Figure 2 and Figure S1, Table S2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the remaining 14 RCTs, [12][13][14][18][19][20][21][22][23][24][25][26]28,29 intubation was performed under general anesthesia after administration of sedative and neuromuscular blocking agents. Since the evaluated techniques were highly heterogeneous, we decided to perform two main meta-analytic comparisons focused on the devices commonly available in the operating room: (a) direct, traditional Macintosh laryngoscopy versus other techniques (three RCTs; Figure 2) and (b) videolaryngoscopy versus other techniques (five RCTs; Figure 3).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%